Predhovor k Vojne [Foreword to the War] fragment by Janko Kráľ. Speech from the catacombs vs. poetics of the ruins - Anna Kobylińska (Slovenska Literatura, 2023)
The fragment “Predhovor k Vojne [Foreword to the war]” is part of the literary estate of Janko Kráľ (1822 – 1876), best known under its first editorial title Dráma sveta [Drama of the world]. The fragment has no title in the manuscript and it was not published before 1938. With regards to its genre and poetics, however, the text is a clear example of a Slovak Romantic fragment – an emblematic genre of the Slovak Literary Romanticism. The article bases its interpretation on the culturological and philosophical take on the theory of the point (A. Kunce) and research of the fragment as a genre, especially on its position in the writings of the representative of early Romanticism, Novalis (1772 – 1801) and in German philosophical school in Jena in general. The article tackles “Foreword to the war” as an example of a text in which modern aesthetics (labelled as “the poetics of the ruins”) blends into the theological disposition of Slovak literary practice (figuratively termed as “speech from the catacombs”) which appears to be a modality of Slovak literature within the Romantic paradigm. The analysed fragment testifies to the hermetic and apocalyptic profile of the “Slovak fragment” and in this way addresses the issue of the literary genre of the apocalypse in Slovak Romantic literature.